(untitled) (Journal of Legal Studies, 2018)
The early regression of the fidejussor implies his ability to "turn" against the debtor even before he pays something to the creditor "To turn against‖ in the sense of the new Civil Code, does not mean the right to actually receive a payment before the fidejussor has paid, at least in part, the claim of the creditor in whose favor he has guaranteed. The same principle applies in insolvency proceedings where the fidejussor, who has not paid anything yet, may exercise early regression, but his claim against the debtor will be a potential, conditional one, reason for which it will be included in the debt table under suspensive condition, without voting rights.